Experimental and analytical investigation of hydraulic conductivity, energy dissipation, and drag forces in gradually varied flow conditions through rockfill media - Jafar Chabokpour (Journal of Applied Research in Water and Wastewater)
This paper focuses on the flow of water through rockfill porous media and brings out the effect of various parameters on hydraulic conductivity, friction factors, energy losses, drag coefficients, drag forces, and shear forces for such systems. Laboratory tests on rock materials with median diameters 1.1 cm and 1.8 cm and porosity of 42% and 47%, respectively, showed a nonlinear relationship between hydraulic gradient and pore velocity. The Reynolds numbers were always greater than 2000, thus fully justifying turbulent flow conditions. The obtained results showed that the Darcy-Weisbach friction factor ranged between approximately 0.8 and 0.2 with surfacing velocity. It was observed that energy losses were nonlinear to the Reynolds number; furthermore, they changed from 0.02 to 0.14 m along the media length. Drag coefficient was found to be an inverse of the Reynolds number with approximate values from 2.5 to 0.5. The shear forces along the water surface profile varied generally between 0.2 and 1.0 N/m² for all test runs, depending on the flow conditions and the media characteristics. Calculated hydraulic conductivity ranges from 0.05 to 0.15 m/s and can be explained primarily by variations of the flow depth and changes to the particle size distribution along the channel. It is further found that variations of porosity and flow depth produce a perceivable effect on shear forces along the water surface profile within rockfill media. Vegetation on the bed and bank also influences the resistance owing to flow.